E-120 Institutional and provider variations in 'solumbra technique' used for stroke thrombectomy: a survey analysis. (22nd July 2018) - Male, S; Mehta, T; Quinn, C; Kallmes, D; Siddiqui, A; Turk, A; Grande, A; Tummala, R; Jagadeesan, B
Abstract : Introduction: The 'Solumbra technique' is one of the most common methods for mechanical thrombectomy used in the treatment of large vessel occlusion ischemic strokes. However, the exact technical parameters followed in this technique have not been standardized and wide variations exist between institutions and operators in the implementation of the Solumbra technique. Herein, we have attempted to evaluate these variations in clinical practice, and their effect on self-reported TICI scores following thrombectomy. Methods: An 18-questionnaire survey was designed using Qualtrics software available through our institution. The survey questions were aimed to extract the information regarding technical variations in the performance of Solumbra. The survey allowed individual respondents' to respond while maintaining complete anonymity. After obtaining institutional review board (IRB) approval, the survey link was posted on Society of Neurointerventional Surgery (SNIS) website in 'SNIS Connect', an exclusive member-only forum of SNIS. Results: Over a period of 2 weeks, 70 responses were obtained that were included in final analysis. 26 (37.2%) out of 64 (6 missing) respondents reported using the Solumbra as their preferred technique. Of these, 16 (61.5%) were Neuroradiologists, 3 (11.5%) were Neurosurgeons, 6 (23.1%) were Neurologists and 1 (3.8%) identified themselves as other. Majority of the providers did not use a balloon guide catheter (BGC) 15 (57.7%) when performing Solumbra. ACE 68 was the most preferred intermediate catheter 22 (84.7%) while Marksman was the most preferred microcatheter 11 (42.3%). Majority of the practitioners 17 (65.4%) commence aspiration from intermediate catheter only when retrieving stent-retriever, whereas others perform aspiration throughout. The microcatheter is always removed before aspiration by 15 (57.7%), and left in place by the rest. 25 (96.2%) of the respondents perform aspiration after positioning intermediate catheter at the face of the clot. After stent retriever deployment 5 (19.2%) respondents would wait for ≤2 min, 16 (61.5%) between 2–5 min, and 5 (19.2%) for more than 5 min. The self-reported successful recanalization rates defined as TICI 2B and TICI 3 in Solumbra group were 73.1% compared to 75.5% respondents who do not prefer Solumbra (p=0.81). Conclusion: The study reveals variations within Solumbra technique of mechanical thrombectomy. These variations including the use of BGC do not account for any significant changes in self-reported angiographic outcomes. Further large sample studies to elucidate this in greater detail may help understand the key variations that can affect outcomes. Disclosures: S. Male: None. T. Mehta: None. C. Quinn: None. D. Kallmes: 1; C; Medtronic, MicroVention, NeuroSigma, Shape Memory Therapeutics, IndumedX, Sequent Medical, Neurogami, and NeuroSave. 2; C; Consulting for Medtronic (all funds to the institution); ownership stake in Marblehead Medical. A. Siddiqui: 1; C; Codman and Shurtleff LARGE Aneurysm Randomized Trial, Covidien (now Medtronic) SWIFT PRIME and Solitaire With the Intention For Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-retriever. 2; C; Amnis Therapeutics Ltd., Cerebrotech Medical Systems Inc., Cerenovus (formerly Codman Neurovascular, Neuravi, and Pulsar Vascular), CereVasc LLC, Claret Medical Inc., Corindus Inc., GuidePoint Global. 6; C; Apama Medical, Buffalo Technology Partners Inc., Cardinal Health, Endostream Medical Ltd., International Medical Distribution Partners, Medina Medical Systems, Neuro Technology Investors, StimMed, Val. A. Turk: 1; C; Medtronic, Penumbra, MicroVention, and Stryker. 2; C; Medtronic, Penumbra, MicroVention, and Stryker. A. Grande: None. R. Tummala: None. B. Jagadeesan: 1; C; Microvention, Medtronic. 2; C; Microvention, CvRx.